What Challenges Emerge from Cases Where Children Are Made Subject to a 'Care Order at Home'? - Murphy, Ciarán; Maguinness, Noreen; Stathopoulos, Eoanna (British Journal of Social Work, 2024)
A continued and unprecedented demand for England's child protection services has coincided with increasing numbers of children being made subject to Care Orders within the Family Court. There is a growing understanding of the associated challenges—not least in terms of cost and placement availability. However, there has been limited discussion of the difficulties associated with children being made subject to a Care Order, but who remain living at home with their parents. This article reports on an iterative mixed method study which sought to explore child protection social workers' experiences of 'Care Orders at home'. It discusses the prevalence of 'Care Orders at home' within Northwest England and identifies specific challenges in the context of 'managing child protection partners' expectations'; apparent 'confusion and disempowerment of the child and family' and 'an increased sense of risk' with respect to several of the key stakeholders involved. Implications that emerge from the study are that a 'Care Order at home' might, in some circumstances, be considered as a 'contradictory' and therefore 'confusing' concept, and that it can offer less protection to a child than a care plan for 'No Order' running concurrently to a detailed child protection plan.